2020
DOI: 10.1177/1071100719901119
|View full text |Cite
|
Sign up to set email alerts
|

Extensor Tendon Transfers for Treatment of Foot Drop in Charcot-Marie-Tooth Disease: A Biomechanical Evaluation

Abstract: Background: In Charcot-Marie-Tooth (CMT) disease, selective weakness of the tibialis anterior muscle often leads to recruitment of the long toe extensors as secondary dorsiflexors, with subsequent clawing of the toes. Extensor hallucis longus (EHL) and extensor digitorum longus (EDL) tendon transfers offer the ability to augment ankle dorsiflexion and minimize claw toe deformity. The preferred site for tendon transfer remains unknown. Our goal was to quantify ankle dorsiflexion in the “intact” native tendon st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…[19][20][21][22] Treatment success in the setting of neurologic etiologies such as cerebral palsy and Charcot-Marie-Tooth disease are more guarded with higher proportions of patients failing to walk without assistive braces and higher rates of additional surgical treatment. 6,20,27 This is likely because of the more complex nature of deformity correction and soft-tissue and muscle power balancing in these patients versus an otherwise normal patient who experienced an acute nerve injury. Gait analysis after PT tendon transfer surgeries does show notable strength deficits, with lost dorsiflexion strength (approximately ⅓ that of control subjects), loss of plantar flexion ROM because of some tenodesis effect, and increased medial foot contact pressures.…”
Section: Tendon Transfermentioning
confidence: 99%
See 2 more Smart Citations
“…[19][20][21][22] Treatment success in the setting of neurologic etiologies such as cerebral palsy and Charcot-Marie-Tooth disease are more guarded with higher proportions of patients failing to walk without assistive braces and higher rates of additional surgical treatment. 6,20,27 This is likely because of the more complex nature of deformity correction and soft-tissue and muscle power balancing in these patients versus an otherwise normal patient who experienced an acute nerve injury. Gait analysis after PT tendon transfer surgeries does show notable strength deficits, with lost dorsiflexion strength (approximately ⅓ that of control subjects), loss of plantar flexion ROM because of some tenodesis effect, and increased medial foot contact pressures.…”
Section: Tendon Transfermentioning
confidence: 99%
“…For example, the EDL tendons may be transferred to the dorsum of the foot to provide more advantageous dorsiflexion force while also removing a deforming force for claw toe deformities. 27 Long-term functional success after PT transfer is defined as the ability to walk without an AFO or brace. Most case series have shown that nearly 100% of patients were successful when treated with tendon transfer after a CPN injury.…”
Section: Tendon Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical review of CMT patients with WBCT scans yielded a total of 54 scans in 45 patients. Twenty-seven scans in 24 patients were excluded for the following reasons: previous bony surgery (15), arthritic changes (7), open physes (4), motion artifact (1). After exclusion, 27 scans in 21 patients were included in the study cohort; 6 patients had bilateral WBCTs.…”
Section: Patient Selectionmentioning
confidence: 99%
“…6,11 Biomechanical evaluation of tendon transfers, 3-dimensional (3D) modeling of osteotomies, and a consensus statement detailing the evaluation and treatment of foot and ankle manifestations of CMT highlight the unique challenges presented to surgeons treating these patients. [15][16][17] Despite the increased focus on this disease process, the etiology of the deformity remains relatively unknown. No previous studies have ever demonstrated whether the etiology of these deformities is chronic soft tissue contractures, pathologic bony architecture, or both.…”
Section: Introductionmentioning
confidence: 99%